Neural Field Theory of Corticothalamic Prediction With Control Systems Analysis - Babaie Janvier, Tahereh; Robinson, Peter A. (Frontiers in Human Neuroscience, 2018)
Neural field theory is used to analyze realistic corticothalamic responses to simple visual stimuli. This yields system transfer functions that embody key features in common with those of engineering control systems, which enables interpretation of brain dynamics in data fusion terms. In particular, these features assist in finding internal signals that represent input stimuli and their changes, which are exactly the types of quantities used in control systems to enable prediction of future states, and adjustment of gains to implement attention. Corticothalamic dynamics are shown to be analogous to the classical proportional-integral-derivative (PID) filters that are widely used in engineering.